T-Cell Immune Surveillance in Allogenic Stem Cell Transplant Recipients: Are Whole Blood–Based Assays Ready to Challenge ELISPOT?. (8th November 2020) - Lauruschkat, Chris D; Page, Lukas; Etter, Sonja; Weis, Philipp; Gamon, Florian; Kraus, Sabrina; Einsele, Hermann; Wurster, Sebastian; Loeffler, Juergen
Abstract: We compared the feasibility of 4 cytomegalovirus (CMV)- and Aspergillus -reactive T-cell immunoassay protocols in allogenic stem cell transplant recipients. While enzyme-linked immunospot performed best overall, logistically advantageous whole blood–based assays performed comparably in patients with less severe lymphocytopenia. CMV-induced interferon-gamma responses correlated strongly across all protocols and showed high concordance with serology.